Products comprising lithiated trihydroxylaurite and methods of making such products
By treating the aqueous suspension of aluminum source and lithium salt at low temperature, lithiated trihydroxylite microcrystals with high lithium adsorption capacity are prepared, which solves the problem of limited adsorption capacity of lithiated trihydroxylite materials in the prior art. It realizes efficient extraction and recycling of lithium.
Patent Information
- Application Number
- CN202380038817.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-26
- Filing Date
- 2023-03-06
- Publication Date
- 2024-12-17
AI Technical Summary
The method of preparing lithiated trihydroxylite in the prior art results in the material having a limited lithium adsorption capacity and cannot meet the needs of efficient lithium extraction.
Lithified trihydroxy aluminum with high lithium adsorption capacity was prepared by treating the aqueous suspension of the aluminum source and lithium salt at a temperature below 50°C, controlling the pH and Cl/Al molar ratio, combined with appropriate heating and acidification treatments. Stone microcrystal products.
The high lithium adsorption capacity of lithiated trihydroxylite is achieved, the extraction efficiency of lithium and the stability of the product are improved, and it is suitable for efficient capture and recycling of lithium.
Smart Images

Figure BDA0005121232510000171 
Figure BDA0005121232510000201 
Figure BDA0005121232510000211
Abstract
Description
Technical Field
[0001] The present invention relates to a product comprising lithiated bayerite and a method for preparing a product comprising lithiated bayerite. Prior art
[0002] The use of lithium, especially in batteries, continues to increase.
[0003] Brine is a source of lithium, which needs to be extracted.
[0004] This extraction or capture can be performed using columns packed with active materials that selectively and reversibly capture lithium when the brine comes into contact with it.
[0005] The lithium is then recovered by passing the aqueous solution through these columns. This produces a concentrated lithium solution which will be purified prior to the precipitation step, usually in the form of lithium carbonate.
[0006] Lithium adsorbents, in particular lithiated bayerite, are materials that are advantageously used as active materials to obtain concentrated lithium solutions in extraction columns.
[0007] FR3053264 describes the preparation of (LiCl) x .2Al(OH)3,nH2O, wherein x is from 0.4 to 1 and n is from 0.01 to 10.
[0008] U.S. Patent No. 4,348,295 describes a method for preparing LiX.2Al(OH)3,nH2O, wherein X is an anion which forms an acid by molecular bonding with H or a salt by bonding with a metal ion. The method comprises the steps of reacting hydrated alumina with a concentrated solution of LiX at a temperature above 85°C. However, the material obtained by this method has a limited lithium adsorption capacity.
[0009] There is a need for a process for preparing a product comprising lithiated bayerite which makes it possible to obtain a product having a high lithium adsorption capacity. The object of the present invention is to meet this need. SUMMARY OF THE INVENTION
[0011] According to the invention, this object is achieved by a product comprising, and preferably consisting essentially of:
[0012] - Water, and
[0013] - crystallites, at least a portion of said crystallites, preferably substantially all of said crystallites consist of lithiated bayerite,
[0014] The average size of lithiated bayerite crystallites is 10 nm or more and 25 nm or less, and
[0015] The product has a combined aluminum hydroxide and boehmite content of 10% or less,
[0016] The product contains at least the elements Li, Cl, Al, O and H,
[0017] The elements Li, Cl and Al are present in the dried product in the following amounts, measured by inductively coupled plasma spectroscopy, in percentage by weight:
[0018] -2% <Li<5%,
[0019] -10% <Cl<26%,
[0020] -15% <Al<30%。
[0021] The average size of lithiated bayerite crystallites and the cumulative content of aluminum hydroxide and boehmite of the products were measured after exposure to air at 25°C for 170 hours under atmospheric pressure.
[0022] The dried product was obtained after drying in air at 200°C under atmospheric pressure for 16 hours.
[0023] According to preferred but non-limiting embodiments of the invention, which can be combined with one another if appropriate:
[0024] - The product presents the following chemical analysis, determined on the dry product by inductively coupled plasma spectroscopy, expressed in percentage by weight:
[0025] -Li, in an amount greater than 2% and less than 5%, and
[0026] -Cl, with a content greater than 10% and less than 26%, and
[0027] -Al, in an amount greater than 15% and less than 30%, and
[0028] - Elements other than Li, Cl, Al, O and H, with a content of less than 3%, and
[0029] -O and H, the content is equivalent to 100% of the balance;
[0030] - the average size of lithiated bayerite crystallites is less than 23 nm;
[0031] - a water content of greater than 1%, preferably greater than 5%, preferably greater than 10% and / or preferably less than 95%, preferably less than 80%, preferably less than 70%;
[0032] - the cumulative content of aluminum hydroxide and boehmite is less than or equal to 8%, preferably less than or equal to 5%;
[0033] - the crystalline phase of the product comprises an aluminum hydroxide selected from lithiated bayerite, boehmite, and / or selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof, preferably, the crystalline phase of the product comprises lithiated bayerite and an aluminum hydroxide selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof;
[0034] - the only crystalline phase present in the product is lithiated bayerite;
[0035] - At least 80% by weight of the product consists of water and lithiated bayerite crystallites, aluminum hydroxide and / or boehmite and LiCl and a binder, preferably at least 80% by weight of the product consists of water and lithiated bayerite crystallites and aluminum hydroxide and LiCl and a binder, preferably the product consists of at least 80% by weight of water and lithiated bayerite crystallites and LiCl and a binder, the binder is preferably a polysaccharide, preferably an alginate.
[0036] The invention also relates to a method for manufacturing a product according to the invention and as described above, comprising the following steps:
[0037] a) an aqueous suspension of an aluminum source, preferably an aqueous suspension of a single aluminum source, the aluminum source being selected from boehmite or aluminum hydroxide and mixtures thereof, preferably aluminum hydroxide, if the median size of the aluminum source is greater than 3 μm, the aqueous suspension being ground to a median size of 3 μm or less, the suspension being maintained at a temperature below 50° C. in step a),
[0038] b) raising the pH by adding a base such that the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.20, and after adding the base, maintaining the mixture under stirring at a temperature below 50° C.;
[0039] c) adding a chloride salt such that the molar ratio of Cl provided by the chloride salt to Al present in the mixture is greater than 0.25, and after the introduction of the chloride salt, the mixture is kept stirred at a temperature below 50° C.; the base in step b), the chloride salt in step c) and their respective amounts are selected so as to provide an amount of lithium in the mixture such that the Li / Al molar ratio is greater than or equal to 1;
[0040] d) raising the temperature of the mixture to a temperature greater than or equal to 50° C. and less than or equal to 60° C., time t1 being the time during which the mixture is at a temperature greater than or equal to 50° C.;
[0041] e) maintaining the mixture at a temperature greater than or equal to 50° C. and less than or equal to 60° C. for a time period t2;
[0042] f) optionally, adding an acid to the mixture under stirring so as to reduce the pH of the mixture to 8 or less, the chloride salt, the acid and their respective amounts in step c) being selected so that the Cl / Al molar ratio in the mixture is greater than or equal to 1, the mixture being maintained at a temperature less than or equal to 60° C., the time t3 being the time during which the mixture is at a temperature greater than or equal to 50° C., the molar ratio between the Cl provided by the chloride salt in step c) and the Al present in the mixture being greater than or equal to 0.5 if the process does not comprise said step f);
[0043] g) optionally and preferably filtering the mixture to obtain a paste, said mixture being kept at a temperature less than or equal to 60° C., time t4 being the time the mixture is at a temperature greater than or equal to 50° C.;
[0044] The accumulated time t1+t2+t3+t4=t5 is greater than or equal to 45 minutes and less than 15 hours.
[0045] According to preferred but non-limiting embodiments of the invention, which can be combined with one another if appropriate:
[0046] - step a) comprises grinding an aqueous suspension of an aluminum source chosen from boehmite or aluminum hydroxide and mixtures thereof to obtain a median size of ≤ 1 μm;
[0047] -Time t5 makes the times t1, t2, t3 and t4 satisfy the following relationship: [t1 / (-1.2T1+75)]+[t2 / (-1.2T 20 +75)]+[t3 / (-1.2%0+75)]+[t4 / (-1.2T 40 +75)]≤1, preferably [t1 / (-0.8T1+50)]+[t2 / (-0.8T 20 +50)]+[t3 / (-0.8%0+50)]+[t4 / (-0.8T 40 +50)]≤1, preferably [t1 / (-0.55T1+34.5)]+[t2 / (-0.55T 20 +34.5)]+[t3 / (-0.55%0+34.5)]+[t4 / (-0.55T 40 +34.5)]≤1, and [t1 / (-0.225T1+14.25)]+[t2 / (-0.225T 20 +14.25)]+[t3 / (-0.225T 30 +14.25)]+[t4 / (-0.225T 40 +14.25)]≥1, preferably [t1 / (-0.2T1+13)]+[t2 / (-0.2T 20+13)]+[t3 / (-0.2T30+13)]+[t4 / (-0.2T 40 +13)]≥1, where T1 is the temperature reached by the mixture in step d), T 20 is the average temperature in step e), T 30 is the average temperature in step f), and T 40 is the average temperature of the mixture during time t4;
[0048] - aluminum hydroxide, boehmite and mixtures thereof are the only aluminum source used in all process steps, preferably aluminum hydroxide is the only aluminum source used in all process steps;
[0049] - in step b), the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.25 and less than 10;
[0050] - in step b), after the addition of the base, the pH of the mixture is greater than 9 and less than 13;
[0051] - in step c), the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is less than 10;
[0052] - the base in step b), the chloride salt in step c), and their respective amounts are selected so as to provide in the mixture an amount of lithium such that the Li / Al molar ratio is greater than 1.1 and less than 4;
[0053] - in step d), the time t1 is greater than 5 minutes;
[0054] - in step e), the temperature of the mixture is substantially constant;
[0055] - in step e), time t2 is greater than 40 minutes;
[0056] - in optional step f), at least part of the amount of Cl necessary to obtain a Cl / Al molar ratio greater than or equal to 1 is provided by an acid;
[0057] - in an optional step f), lowering the pH of the mixture to a value below 7.5 and above 6.5;
[0058] - in optional step f), setting the Cl / Al molar ratio in the mixture to a value less than 3;
[0059] - in optional step f), the temperature of the mixture is substantially constant;
[0060] - in optional step f), the time t3 is greater than 5 minutes;
[0061] - in step g), time t4 is less than 15 minutes;
[0062] - Steps a) and b) are performed simultaneously;
[0063] - Steps a), b) and c) are performed simultaneously;
[0064] - the method comprises, after step g), a step h) of shaping the starting charge comprising the paste obtained at the end of step g) into the form of an object or a coating, preferably into the form of an object, and optionally a step i) of reducing the water content of the object or coating;
[0065] - in step h), the starting charge comprises a binder, preferably a polysaccharide comprising groups capable of forming ionic bonds with a gelling agent to form a gelling polysaccharide, preferably a polysaccharide selected from alginates;
[0066] - Steps h) and i) are carried out at least partially simultaneously.
[0067] Finally, the invention relates to a device for collecting lithium, in particular an extraction tower, comprising a product according to the invention or a product obtained by a process according to the invention as described above.
[0068] definition
[0069] - As shown in ICDD PDF 00-031-0700, the compound of formula LiCl.2Al(OH)3.XH2O is called "lithiated bayerite" and, by extension, compounds having a molar ratio of lithium to aluminum, Li / Al, other than 0.5, are called by the same name. In some modes, it may be less than 0.5. According to other modes, it may be greater than 0.5.
[0070] - Compounds of formula Al(OH)3 are called "aluminum hydroxide." Gibbssite, bayerite, triclinic gibbssite, and nordstrandite are aluminum hydroxides.
[0071] -Compounds of the formula γ-AlO(OH) are called "boehmite".
[0072] - Calculate the "cumulative content of aluminum hydroxide and boehmite" (in %) in the product according to the following formula (1):
[0073] T=100*(A HA +A BO ) / (A HA +A BO +A BL ) (1)
[0074] in
[0075] -A HAis the sum of the areas of the aluminum hydroxide phase measured on the X-ray diffraction pattern of the product, obtained, for example, from Panalytical, of the X'Pert diffractometer type, with a copper DX tube, after elimination of the Kα2 line, without deconvolution treatment. The area of the aluminum hydroxide phase is that of the diffraction peak located within an angular range 2θ substantially equal to 18.3°;
[0076] -A BO is the area of the boehmite diffraction peak located within an angular range 2θ substantially equal to 14° measured on the same graph after elimination of the Kα2 line and without deconvolution;
[0077] -A BL is the area of the diffraction peak of the lithiated bayerite located in the plane (003) within an angular range 2θ substantially equal to 11.3°, measured on the same pattern after elimination of the Kα2 line and without deconvolution.
[0078] - "Polysaccharides", according to the classical definition, are polymers composed of chains of sugar units linked by glycosidic bonds.
[0079] The term "gellable polysaccharide" is a polysaccharide that is capable of forming a gel under the action of a gelling agent.
[0080] - Gelling polysaccharides are produced by the association of polysaccharide chains under the action of a gelling agent. For example, alginate has the formula (C6H7O6 - ) n Alginate contains carboxyl groups COO - Polysaccharide chain. Ca 2+ Calcium ions (gelling agent) react with the two chains of alginate, namely with the carboxyl COO - The reaction causes the alginate chains to polymerize and the molecules to bind to each other. The reaction allows gelation to occur.
[0081] The term "dried product" means the product obtained after drying at 200°C for 16 hours in air (at atmospheric pressure), the drying being conventionally carried out in an oven for example.
[0082] - The "median size" of a particle powder or particle suspension is the size that separates the particles of the powder into first and second populations of equal weight, wherein the first and second populations contain only particles having a size greater than or less than the median size, respectively. The median size can be assessed, for example, using a laser particle size analyzer.
[0083] Unless otherwise stated, all percentages in this specification are percentages by weight.
[0084] The verbs "to include," "to include," and "to have" are to be interpreted broadly and without limitation, unless otherwise indicated.
[0085] Detailed Description
[0086] The product according to the invention has one or more of the following optional features:
[0087] a water content of greater than 1%, preferably greater than 5%, preferably greater than 10% and / or preferably less than 95%, preferably less than 90%, preferably less than 80%, preferably less than 70%, or even less than 60%. The water content is the mass loss expressed as a percentage after drying at 200° C. in air at atmospheric pressure for 16 hours;
[0088] - an average size of lithiated bayerite crystallites of less than 23 nm, preferably less than 20 nm;
[0089] - the cumulative content of aluminum hydroxide and boehmite is 8% or less, preferably 5% or less, preferably substantially zero;
[0090] - The crystalline phase comprises, preferably consists of, lithiated bayerite, boehmite and / or an aluminium hydroxide selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof, preferably gibbsite. Preferably, the crystalline phase comprises, preferably consists of, lithiated bayerite and an aluminium hydroxide selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof, preferably gibbsite. Preferably, the only crystalline phase is lithiated bayerite. After exposing the product to air at atmospheric pressure and 25°C for 170 hours, the crystalline phase, the cumulative content of aluminium hydroxide and boehmite and the size of the lithiated bayerite crystallites are determined for the product;
[0091] - After drying in air at 200°C under atmospheric pressure for 16 hours, the content of Li, Cl and Al elements present in the product is the following weight percentages:
[0092] - Li: preferably greater than 2.5%, preferably greater than 3%, and / or preferably less than 4.5%, preferably less than 4%, and
[0093] -Cl: preferably greater than 11%, preferably greater than 13% and / or preferably less than 24%, preferably less than 22%, and
[0094] -Al: preferably greater than 17%, preferably greater than 19% and / or preferably less than 28%, preferably less than 26%;
[0095] - The following chemical analyses were determined by inductively coupled plasma spectroscopy after drying at 200°C in air at atmospheric pressure for 16 hours, expressed in weight percent:
[0096] -Li, in an amount greater than 2%, preferably greater than 2.5%, preferably greater than 3% and less than 5%, preferably less than 4.5%, preferably less than 4%, and
[0097] -Cl, the content is greater than 10%, preferably greater than 11%, preferably greater than 13% and less than 26%, preferably less than 24%, preferably less than 22%, and
[0098] - Al, in an amount greater than 15%, preferably greater than 17%, preferably greater than 19% and less than 30%, preferably less than 28%, preferably less than 26%, and
[0099] - elements other than Li, Cl, Al, O and H in an amount less than 3%, preferably less than 2%, preferably less than 1%, and
[0100] -O and H, the content is equivalent to 100% of the balance;
[0101] - after drying in air at 200° C. for 16 hours at atmospheric pressure, the product has a Li / Al mass ratio greater than 0.1, preferably greater than 0.15 and / or preferably less than 0.3, preferably less than 0.25;
[0102] - after drying in air at 200°C for 16 hours at atmospheric pressure, the product has a Li / Cl mass ratio greater than 0.08, preferably greater than 0.1, preferably greater than 0.13, preferably greater than 0.15 and / or preferably less than 0.4, preferably less than 0.3, preferably less than 0.25;
[0103] - the product consists of at least 80% by weight, preferably greater than 85% by weight, preferably greater than 90% by weight, preferably greater than 95% by weight, preferably greater than 99% by weight of water and lithiated bayerite crystallites, as well as aluminum and / or boehmite hydroxide and LiCl, and a binder (preferably a polysaccharide, preferably a gelling polysaccharide, preferably an alginate, preferably a gelling alginate). Preferably, at least 80% by weight, preferably greater than 85% by weight, preferably greater than 90% by weight, preferably greater than 95% by weight, preferably greater than 99% by weight of water and the crystallites and aluminum hydroxide and LiCl and a binder, preferably a polysaccharide, preferably a gelling polysaccharide, preferably an alginate, preferably a gelling alginate. Preferably, at least 80% by weight, preferably greater than 85% by weight, preferably greater than 90% by weight, preferably greater than 95% by weight, preferably greater than 99% by weight of water and the crystallites and LiCl and a binder (preferably a polysaccharide, preferably an alginate);
[0104] - the product is in the form of an object in the form of a cylinder, a multilobate, a ring or a sphere. Preferably, the object has a larger dimension of less than 100 mm, preferably less than 80 mm, preferably less than 50 mm, preferably less than 30 mm, or even less than 10 mm, and / or a smaller dimension greater than 1 μm or even greater than 10 μm (micrometers) measured in a plane perpendicular to the direction of the largest dimension;
[0105] - the product is in the form of a coating deposited on a support. Preferably, the coating has a thickness greater than 10 μm, preferably greater than 50 μm, preferably greater than 100 μm, preferably greater than 200 μm, and preferably less than 1 mm, preferably less than 500 μm. Preferably, the support is made of a material chosen from ceramics, metals, organic products, in particular polymers, and mixtures thereof;
[0106] - When the product contains a polysaccharide, preferably a gelling polysaccharide, preferably alginate or pectin, preferably gelling alginate or gelling pectin, preferably alginate, preferably gelling alginate, the amount of the polysaccharide, preferably gelling polysaccharide, by weight is greater than or equal to 0.1%, preferably greater than or equal to 0.2%, preferably greater than or equal to 0.3% and less than or equal to 5%, preferably less than or equal to 4%, preferably less than or equal to 3%, preferably less than or equal to 2%, preferably less than or equal to 1%. The presence of polysaccharides, alginate in the adhesive can be demonstrated, for example, by size exclusion chromatography.
[0107] The product according to the invention can be manufactured according to the method according to the invention, which method comprises the above-mentioned steps a) to g), in particular and preferably steps a) to i).
[0108] In step a), an aluminum source selected from boehmite or aluminum hydroxide and mixtures thereof, preferably aluminum hydroxide, is placed in an aqueous suspension, and
[0109] If the median size of the aluminum source is greater than 3 μm, the aqueous suspension is ground to obtain a median size of less than or equal to 3 μm, preferably less than or equal to 2 μm, preferably less than or equal to 1 μm, preferably less than or equal to 0.7 μm, preferably less than or equal to 0.5 μm,
[0110] In this step a), the suspension is kept at a temperature below 50°C
[0111] The aqueous suspension of the aluminum source and the grinding of the aqueous suspension may be performed simultaneously.
[0112] Preferably, grinding of the aqueous suspension is carried out if the median size of the aluminum source is greater than 2 μm, greater than 1 μm.
[0113] In a preferred embodiment, an aqueous suspension of an aluminum source selected from boehmite or aluminum hydroxide and mixtures thereof, preferably aluminum hydroxide, is ground to a median size of ≤ 1 μm, during which step the suspension is maintained at a temperature below 50°C.
[0114] Preferably the aluminium hydroxide is gibbsite.
[0115] Preferably, aluminum hydroxide, boehmite and mixtures thereof are the only aluminum sources used in all steps of the process according to the invention. Preferably, aluminum hydroxide is the only aluminum source used in all steps of the process according to the invention.
[0116] Preferably, the median size obtained after grinding is less than or equal to 0.7 μm, preferably less than or equal to 0.5 μm.
[0117] Preferably, during step a), the suspension is maintained at a temperature greater than 15°C, preferably greater than or equal to 20°C.
[0118] Grinding can be performed according to any technique known to those skilled in the art, for example by wet grinding.
[0119] In step b), the pH of the mixture obtained at the end of step a) is increased by adding a base so that the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.20. After the addition of the base, the mixture is kept stirred at a temperature below 50°C.
[0120] Preferably, the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.25, preferably greater than 0.4, preferably greater than or equal to 0.5, and / or preferably less than 10, preferably less than 9, preferably less than 8, preferably less than 7, preferably less than 6, preferably less than 5, preferably less than 4, preferably less than 3, preferably less than 2, preferably less than 1.5.
[0121] Preferably, in particular when the aluminium source used in step a) is aluminium hydroxide, the pH of the mixture after addition of the base is greater than 9, preferably greater than 10, and preferably less than 13, preferably less than 12.
[0122] Preferably, the base does not contain the element aluminum.
[0123] Also preferably, the base used is selected from NaOH, LiOH, NH4OH, KOH, Ca(OH)2, RbOH, CsOH, Sr(OH)2, Ba(OH)2, Mg(OH)2 and mixtures thereof. Preferably, the base is selected from NaOH, LiOH, NH4OH and mixtures thereof. Preferably, the base is LiOH.
[0124] Preferably, the stirring time is greater than 5 minutes, preferably greater than 10 minutes, preferably greater than 15 minutes, and preferably less than 5 hours.
[0125] Preferably, the stirred mixture is maintained at a temperature greater than 15°C, preferably greater than or equal to 20°C, preferably greater than or equal to 25°C.
[0126] In one embodiment, steps a) and b) are performed simultaneously.
[0127] In step c), a chloride salt is added to the mixture so that the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is greater than 0.25, and after the introduction of the chloride salt, the mixture is kept stirred at a temperature of less than 50° C. If the process does not include step f), the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is greater than or equal to 0.5, preferably greater than or equal to 1, preferably greater than 1.
[0128] In one embodiment, the method comprises step f).
[0129] Preferably, the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is greater than 0.25, preferably greater than 0.4, preferably greater than 0.5, and preferably less than 10, preferably less than 9, preferably less than 8, preferably less than 7, preferably less than 6, preferably less than 5, preferably less than 4, preferably less than 3, preferably less than 2, preferably less than 1.5.
[0130] Preferably the chloride salt does not contain the element aluminum.
[0131] Also preferably, the chloride salt is selected from LiCl, NaCl, KCl, CaCl2, NH4Cl, MgCl2 and mixtures thereof, preferably selected from LiCl, NaCl, KCl, CaCl2 and mixtures thereof. Preferably, the chloride salt is LiCl.
[0132] Preferably, the stirring time is greater than 5 minutes, preferably greater than 10 minutes, preferably greater than 15 minutes, and preferably less than 48 hours.
[0133] Preferably, the stirred mixture is maintained at a temperature greater than 15°C, preferably greater than or equal to 20°C, preferably greater than or equal to 25°C.
[0134] The base in step b), the chloride salt in step c) and their respective amounts are selected so as to provide an amount of lithium in the mixture such that the Li / Al molar ratio is greater than or equal to 1. Preferably, the molar ratio is greater than 1.1, preferably greater than 1.2, and preferably less than 4, preferably less than 2.
[0135] In one embodiment, steps a), b) and c) are performed simultaneously.
[0136] In step d), the temperature of the mixture is raised to a temperature T1 greater than or equal to 50°C and less than or equal to 60°C, time t1 being the time during which the mixture is at a temperature greater than or equal to 50°C.
[0137] Preferably, the mixture is kept stirred during step d).
[0138] Preferably, the time t1 is greater than 5 minutes, preferably greater than 10 minutes, and preferably less than 15 hours, preferably less than 10 hours.
[0139] In step e), the mixture is maintained at a temperature greater than or equal to 50° C. and less than or equal to 60° C. for a time t2.
[0140] Preferably, the mixture is kept stirred during step e).
[0141] Let T 20 is the average temperature during step e).
[0142] Preferably, during step e), the temperature of the mixture is substantially constant and equal to T 21 .
[0143] Preferably, time t2 is greater than 40 minutes, preferably greater than 45 minutes, preferably greater than 60 minutes, and preferably less than 10 hours, preferably less than 7 hours.
[0144] In step f), optionally, an acid is added to the mixture under stirring so as to reduce the pH of the mixture to a value less than or equal to 8, preferably less than or equal to 7.5, and preferably greater than or equal to 6, preferably greater than or equal to 6.5, the chloride salt in step c), the acid, and their respective amounts are selected so that the Cl / Al molar ratio in the mixture is greater than or equal to 1, preferably greater than 1, the mixture is maintained at a temperature less than or equal to 60° C., and time t3 is the time in which the mixture is at a temperature greater than or equal to 50° C.
[0145] In a preferred embodiment, at least part of the amount of Cl necessary to obtain a Cl / Al molar ratio greater than or equal to 1, preferably greater than 1, is provided by the acid.
[0146] In one embodiment, several acids are added to the mixture. In this embodiment, one acid may include Cl, preferably includes Cl.
[0147] Preferably, the acid is selected from HCl, H2SO4, HNO3, HI, HBr, HClO4, HClO3, HMnO4, H2MnO4 and mixtures thereof, preferably selected from HCl, HNO3, HBr, HClO4, HClO3 and mixtures thereof. Preferably, the acid is HCl.
[0148] Preferably, the Cl / Al molar ratio in the mixture is adjusted to a value less than 3, preferably less than 2.
[0149] Let T 30 is the average temperature during step f).
[0150] Preferably, during step f), the temperature of the mixture is substantially constant and equal to T 31 .
[0151] Preferably, the time t3 is greater than 5 minutes, preferably greater than 10 minutes, and preferably less than 60 minutes, preferably less than 40 minutes.
[0152] The implementation of step f) depends in particular on the nature of the lithium source for which the lithium extraction is envisaged, in particular its pH. For example, if the pH of the lithium source is less than 7, the method according to the invention preferably comprises step f).
[0153] The mixing carried out in steps b), c), d), e) and optionally f) can be carried out according to any known technique, for example with the aid of a mixer or a grinder, preferably on a wet basis, with control and regulation of the temperature of the mixture.
[0154] In step g), optionally and preferably, the mixture is filtered to obtain a paste, the mixture being maintained at a temperature less than or equal to 60° C., time t4 being the time the mixture is at a temperature greater than or equal to 50° C.
[0155] T 40 is the average temperature of the mixture during time t4.
[0156] Preferably, during step g), the temperature of the mixture is substantially constant and equal to T 41 .
[0157] In one embodiment, the temperature of the mixture is reduced to below 50°C before initiating filtration.
[0158] In a preferred embodiment, time t4 is less than 15 minutes, preferably less than 10 minutes, preferably less than 5 minutes.
[0159] Any known filtering technique can be used in this step, in particular filter presses, centrifuges, belt filters, drum filters.
[0160] At the end of optional step g), the cumulative time t1+t2+t3+t4 or t5, ie the time the mixture has been exposed to a temperature greater than or equal to 50° C. and less than or equal to 60° C., is greater than or equal to 45 minutes and less than 15 hours.
[0161] Preferably, time t5 is greater than 50 minutes, preferably greater than 55 minutes, preferably greater than 1 hour.
[0162] The time t5 is a function of the temperature and the median size of the aluminum source. A person skilled in the art will know how to adjust the time t5 as the temperature and the median size of the aluminum source change. For example, if the median size of the aluminum source is less than 1 μm, and in step g), t4 is 0, and the temperature in steps d), e) and f) is 50°C (in other words, T1=T 21 =T 31 =50°C), the time t5 is greater than 3 hours and less than 15 hours, preferably less than 10 hours, preferably less than 7 hours. For example, if the median size of the aluminum source is less than 1 μm, and the temperature in steps d), e) and f) is 60°C (in other words T1 = T 21 = =T 31 =60°C), and if time t4 is preferably less than 15 minutes, preferably less than 10 minutes, preferably less than 5 minutes, then time t5 is greater than or equal to 45 minutes, preferably greater than 1 hour and less than 3 hours, preferably less than 2 hours, preferably less than 1.5 hours.
[0163] The time t5 is preferably such that the times t1, t2, t3 and t4 satisfy the following relationship:
[0164] [t1 / (-1.2T1+75)]+[t2 / (-1.2T 20 +75)]+[t3 / (-1.2T 30 +75)]+[t4 / (-1.2T 40 +75)]≤1 and [t1 / (-0.225T1+14.25)]+[t2 / (-0.225T 20 +14.25)]+[t3 / (-0.225T 30 +14.25)]+[t4 / (-0.225T 40 +14.25)]≥1.
[0165] Preferably, time t5 makes time t1, t2, t3 and t4 satisfy the following relationship:
[0166] [t1 / (-0.8T1+50)]+[t2 / (-0.8T 20 +50)]+[t3 / (-0.8T 30 +50)]+[t4 / (-0.8T 40 +50)]≤1, preferably [t1 / (-0.55T1+34.5)]+[t2 / (-0.55T 20 +34.5)]+[t3 / (-0.55T 30 +34.5)]+[t4 / (-0.55T 40 +34.5)]≤1 and / or [t1 / (-0.2T1+13)]+[t2 / (-0.2T20 +13)]+[t3 / (-0.2T 30 +13)]+[t4 / (-0.2T 40 +13)]≥1.
[0167] In one embodiment, the temperatures in steps d), e) and optionally f) are substantially constant and are equal to T1, T2, T3, T4, T5, T6, T7, T8, T9, T10, T11, T12, T13, T14, T15, T16, T17, T18, T19, T20, T21, T31, T42, T53, T19, T21, T31, T42, 21 and T 31 , and time t5 makes time t1, t2, t3 and t4 satisfy the following relationship:
[0168] [t1 / (-1.2T1+75)]+[t2 / (-1.2T 21 +75)]+[t3 / (-1.2T 31 +75)]+[t4 / (-1.2T 40 +75)]≤1 and [t1 / (-0.225T1+14.25)]+[t2 / (-0.225T 21 +14.25)]+[t3 / (-0.225T 31 +14.25)]+[t4 / (-0.225T 40 +14.25)]≥1.
[0169] Preferably, in the embodiment, time t5 is such that times t1, t2, t3 and t4 satisfy the following relationship:
[0170] [t1 / (-0.8T1+50)]+[t2 / (-0.8T 21 +50)]+[t3 / (-0.8T 31 +50)]+[t4 / (-0.8T 40 +50)]≤1, preferably [t1 / (-0.55T1+34.5)]+[t2 / (-0.55T 21 +34.5)]+[t3 / (-0.55T 31 +34.5)]+[t4 / (-0.55T 40 +34.5)]≤1 and / or [t1 / (-0.2T1+13)]+[t2 / (-0.2T 21 +13)]+[t3 / (-0.2T 31 +13)]+[t4 / (-0.2T 40 +13)]≥1.
[0171] These relationships advantageously make it possible to improve the lithium adsorption capacity of the product according to the invention.
[0172] In one embodiment, the temperature in steps d), e) and f) is equal to 60°C (in other words, T1 = T 21 =T 31 =60°C), time t4 is preferably less than 15 minutes, preferably less than 10 minutes, preferably less than 5 minutes, and the cumulative time t1+t2+t3+t4, in other words t5, the time for which the mixture has been exposed to a temperature greater than or equal to 50°C and less than or equal to 60°C is greater than or equal to 45 minutes, preferably greater than 1 hour and less than 3 hours, preferably less than 2 hours, preferably less than 1.5 hours.
[0173] In one embodiment, the temperature in steps d), e) and f) is equal to 50°C (in other words, T1 = T 21 = =T 31 =50°C), time t4 is equal to 0, and the cumulative time t1+t2+t3, in other words t5, the time for which the mixture has been exposed to a temperature equal to 50°C is greater than 3 hours and less than 15 hours, preferably less than 10 hours, preferably less than 7 hours.
[0174] In a preferred embodiment, the process according to the invention comprises, after step g), a step h) of shaping the starting charge comprising the paste obtained at the end of step g) into the form of an object or a coating, and optionally a step i) for reducing the water content of said object.
[0175] In step h), the starting charge comprising the paste obtained at the end of step g) is shaped into the form of an object or a coating deposited on a support.
[0176] The shaping can be carried out according to any technique known to the person skilled in the art, such as extrusion, granulation, pressing, casting, atomization, screen printing, casting or dispensing, especially when obtaining an object, or by stamping, lamination, coating, granulation, especially when obtaining a coating deposited on a support.
[0177] In one embodiment, the starting filler does not contain a binder.
[0178] In one embodiment, the raw material also comprises a binder, preferably a polysaccharide, comprising a fraction capable of forming ionic bonds with the gelling agent to form a gelling polysaccharide, in particular in such an amount that the weight ratio of the amount of said polysaccharide to the total amount of said polysaccharide and of the paste considered as dry matter obtained at the end of step g) is greater than or equal to 0.1% and less than or equal to 5%. Preferably, said mass ratio is greater than or equal to 0.2%, preferably greater than or equal to 0.3%, and preferably less than or equal to 4%, preferably less than or equal to 3%, preferably less than or equal to 2%, preferably less than or equal to 1%.
[0179] Preferably, the polysaccharide groups capable of forming ionic bonds with the gelling agent are carboxylate COO- groups.
[0180] Preferably, the polysaccharide comprises groups capable of forming ionic bonds with a gelling agent selected from divalent cations, trivalent cations (e.g. Fe or Al cations) and mixtures thereof, preferably from alkaline earth metal cations, preferably from Ca, Sr, Ba, Mg cations and mixtures thereof. Preferably, the polysaccharide comprises groups capable of forming ionic bonds with Ca cations.
[0181] Preferably, the polysaccharide comprising groups capable of forming ionic bonds with the gelling agent is selected from alginate and pectin.
[0182] Preferably, the polysaccharide comprising a group capable of forming an ionic bond with a gelling agent is selected from alginates, preferably from sodium alginate, potassium alginate, ammonium alginate, calcium alginate, and mixtures thereof, preferably from sodium alginate, potassium alginate, ammonium alginate, and mixtures thereof. Preferably, the alginate is ammonium alginate.
[0183] In the method according to the invention, a polysaccharide comprising groups capable of forming ionic bonds with a gelling agent, preferably alginate, may be provided in the form of a solution.
[0184] As is well known to a person skilled in the art, in addition to the paste obtained at the end of step g) and the polysaccharide comprising groups capable of forming ionic bonds with the gelling agent (preferably alginate), the starting filler may comprise: a solvent and / or a plasticizer and / or a lubricant, the nature and amount of which are suitable for the shaping method of step h).
[0185] Preferably, the solvent is water.The amount of solvent is adapted to the shaping method carried out in step h) and to the presence of a polysaccharide comprising groups capable of forming ionic bonds with the gelling agent in the starting charge.
[0186] In one embodiment, in particular when the starting charge contains an amount of solvent, preferably water, which is too large compared to the shaping process envisaged in step h), a step of removing part of the solvent may be carried out before step h).
[0187] In one embodiment, step f) makes it possible to obtain a paste having a solvent content, preferably a water content, suitable for the shaping method envisaged in step h).
[0188] The starting filler optionally contains a plasticizer.
[0189] Preferably, the plasticizer content is from 0.1% to 10% by weight, preferably from 0.5% to 5% by weight, preferably from 0.5% to 2% by weight, based on the weight of the paste obtained at the end of step g) of the initial charge.
[0190] All plasticizers customary for producing porous ceramic products may be used, for example polyethylene glycols, polyolefin oxides, hydrogenated oils, alcohols, in particular glycerol and glycols (ethylene glycol), esters and mixtures thereof.
[0191] In a preferred embodiment, the starting filler contains no plasticizer.
[0192] The starting charge optionally contains a lubricant. Preferably, the lubricant content is from 0.1% to 10% by weight, preferably from 0.5% to 5% by weight, preferably from 0.5% to 2% by weight, based on the weight of the paste obtained at the end of step g) of the starting charge.
[0193] All lubricants customary for producing porous ceramic products may be used, for example petrolatum and / or glycerol and / or waxes.
[0194] The presence and nature of lubricants and / or plasticizers depends in particular on the shaping technique used in step h).
[0195] In a preferred embodiment, the feedstock is free of lubricants.
[0196] In a preferred embodiment, the feedstock does not contain any other components than the paste obtained at the end of step g), the binder (preferably a polysaccharide) and the solvent.
[0197] The mixing of the various components of the starting materials can be carried out according to any technique known to the person skilled in the art, for example in a mixer, preferably in a high intensity mixer or in a Z-arm mixer, in a turbulent, in a jar mill with balls, preferably alumina beads. The mixing is preferably carried out in a high intensity mixer or in a Z-arm mixer.
[0198] The total mixing time is preferably greater than 5 minutes, and preferably less than 30 minutes, preferably less than 20 minutes.
[0199] Step h) may be preceded by a step of removing at least part of the solvent, in order to adapt the amount of solvent, preferably water, to the shaping technique envisaged in step h). All known techniques for at least partial removal of the solvent, preferably water, may be used, preferably drying, preferably in air, at atmospheric pressure. Preferably, the maximum temperature reached during said drying is greater than 20° C. and preferably less than 100° C.
[0200] The object obtained after shaping can be in the form of a cylinder, a multilobate, a ring or a sphere. Preferably, the object has a larger dimension of less than 100 mm, preferably less than 80 mm, preferably less than 50 mm, preferably less than 30 mm, or even less than 10 mm, and preferably greater than 1 mm, and / or a smaller dimension of greater than 1 μm or even greater than 10 μm (micrometers) measured in a plane perpendicular to the direction of the largest dimension.
[0201] The thickness of the coating obtained after shaping may be greater than 10 μm, preferably greater than 50 μm, preferably greater than 100 μm, preferably greater than 200 μm, and preferably less than 1 mm, preferably less than 500 μm. Preferably, the support is made of a material selected from ceramics, metals, organic products, in particular polymers, and mixtures thereof.
[0202] The preferred embodiments will now be described.
[0203] - In the preferred embodiment, in step h), the starting filler contains a polysaccharide, preferably alginate, and is shaped to obtain a preform, the shaping being carried out according to any technique known to those skilled in the art, such as extrusion, granulation, pressing, casting, atomization, screen printing, casting or glue dripping. Preferably, in the embodiment, the shaping is carried out by screen printing.
[0204] Then, still according to this preferred embodiment, the preform is brought into contact with a solution comprising a gelling agent capable of gelling a polysaccharide, preferably an alginate.
[0205] Solutions comprising gelling agents capable of gelling polysaccharides, preferably alginate, are well known to those skilled in the art.
[0206] The gelling agent is preferably selected from divalent cations, trivalent cations and mixtures thereof, preferably from alkaline earth metal cations, preferably from Ca, Sr, Ba, Mg cations and mixtures thereof. Preferably, the gelling agent is a Ca cation.
[0207] The solution containing the gelling agent is preferably selected from a solution comprising a divalent cation salt, a solution comprising a trivalent cation salt or a lithium source from which lithium is extracted, preferably a brine, in particular when it contains such cations.
[0208] Preferably, the solution comprising a salt of a divalent cation or a trivalent cation is selected from an iodide solution of said cation and / or a chloride solution of said cation.
[0209] Preferably, the gelling solution is a solution comprising alkaline earth metal cation iodide and / or alkaline earth metal cation chloride. Also preferably, the gelling solution is a solution comprising alkaline earth metal cation chloride, preferably a solution comprising calcium chloride.
[0210] In a preferred embodiment, the gelled solution is a lithium source from which the lithium is extracted, preferably a brine from which the lithium is collected, especially when the latter comprises divalent and / or trivalent cations.
[0211] In another possible embodiment, the gelling solution is a calcium chloride solution, the calcium chloride concentration of which is preferably greater than 1 mol / l of the solution, preferably greater than 2 mol / l of the solution.
[0212] The preform may be brought into contact with the gelling solution, for example by dipping the preform into a bath of the gelling solution or by spraying the preform with the gelling solution.
[0213] In one embodiment, forming of the preform and contacting with the gelling solution occur simultaneously, particularly when the preform is achieved by dropwise gelling.
[0214] In step i), optionally and preferably, the water content of the object or coating obtained at the end of step h) is reduced.
[0215] This reduction in water content can be carried out by drying.
[0216] Preferably, the maximum temperature reached during said drying is greater than 20°C, and preferably less than 100°C, preferably less than 80°C, preferably less than 60°C.
[0217] Also preferably, the drying cycle has a plateau at said highest temperature reached. The holding time at the plateau is preferably greater than 5 seconds, and preferably less than 20 hours. Drying is preferably carried out in air at atmospheric pressure.
[0218] Preferably, the water content of the product at the end of step i) is greater than 1%, preferably greater than 5%, preferably greater than 10%, and preferably less than 60%, based on the mass of the product.
[0219] In one embodiment, steps h) and i) may be performed at least partially simultaneously.
[0220] The invention also relates to a product according to the invention obtainable by the process according to the invention. Example
[0221] To illustrate the present invention, the following non-limiting examples are given.
[0222] The properties of the crystalline phases of the objects of the examples were determined by the following conventional methods:
[0223] The product of Example was previously exposed to air at 25° C. and atmospheric pressure for 170 hours.
[0224] Acquisition was performed with an X'Pert-type device from Panalytical equipped with a copper anode over an angular range 2θ of 5° to 80°, with a step size of 0.017° and a counting time of 300 s / step. The front lens had a fixed divergence slit of 0.25°, a Soller slit of 0.02 rad, a 10 mm mask and a fixed antiscatter slit of 0.5°. The sample rotated. The rear optics featured a fixed antiscatter slit of 0.25°, a Soller slit of 0.02 rad and a nickel filter.
[0225] The diffraction patterns were then qualitatively analyzed using EVA software and the ICDD2016 database.
[0226] ICDD2016 PDF data sheet 00-031-0700 identifies the phase (LiCl)·2Al(OH)3,xH2O.
[0227] The demonstrated crystalline phase of lithiated bayerite may show a slight angular shift relative to the peaks of the data table, which is in particular a result of the amount of Li intercalated in the lithiated bayerite structure.
[0228] The average size of the lithiated bayerite crystallites D of the product of the example is usually determined by X-ray diffraction on a powder of the product (which powder was previously exposed to air at 25° C. and atmospheric pressure for 170 hours) using an X'Pert type apparatus from Panalytical using the following Debye-Scherrer equation:
[0229]
[0230] -K is equal to 0.89,
[0231] -λ is the wavelength of the X-rays, which here is equal to the wavelength of copper, or 1.54 angstroms,
[0232] -B is the half-height width of the peak of the plane (003) of lithiated bayerite (ICCD database PDF data sheet 00-031-0700), in degrees,
[0233] - b is the half-width at half-height of the peak of the single-crystal silicon standard used, measured here to be equal to 0.05°, and
[0234] -2θ is the angle, measured in degrees, of the peak intensity maximum corresponding to the plane (003) of lithiated bayerite.
[0235] Diffraction patterns for single crystal silicon standards and examples were obtained over an angular range 2θ of 5° to 80° with a step size of 0.017° and a counting time of 300 seconds / step for the examples and 100 seconds / step for the single crystal silicon standards. The front lens had a fixed divergence slit of 0.25°, a Soller slit of 0.02 rad, a 10 mm mask, and a fixed antiscatter slit of 0.5°. The sample rotated. The rear optics featured a fixed antiscatter slit of 0.25°, a Soller slit of 0.02 rad, and a nickel filter.
[0236] After removing the Kα2 line, the half-width at half maximum of the peak was determined using the EVA software, and the average size of the lithiated bayerite crystallites was determined using the FWHM function.
[0237] The determination of the cumulative content of aluminum hydroxide and boehmite is carried out on the basis of the same X-ray diffraction pattern as that used to detect the presence of the crystalline phases. After removing the Kα2 line and using the EVA software, it is possible to measure the area A of the aluminum hydroxide diffraction peak present in the angular range 2θ substantially equal to 18.3°. HA , the area A of the boehmite diffraction peak in the angular range 2θ substantially equal to 14° BO , and the area A of the lithiated bayerite diffraction peak in the angular range 2θ substantially equal to 11.3° BL The cumulative content of aluminum hydroxide and boehmite is then calculated according to the formula (1) given above:
[0238] T=100*(A HA +A BO ) / (A HA +A BO +A BL ) (1)
[0239] Therefore, when the product does not contain aluminum hydroxide or boehmite, the cumulative content of aluminum hydroxide and boehmite is zero.
[0240] The contents of the various elements present in the products of the examples, with the exception of the elements O and H, were determined by inductively coupled plasma spectroscopy (or "ICP") on the products dried in air at 200°C at atmospheric pressure for 16 hours.
[0241] The water content is determined as the mass loss, expressed as a percentage, after drying in air at 200° C. at atmospheric pressure for 16 hours. After this drying, the product is referred to as “dried”.
[0242] The contents of elements other than H and O (partial Li, Cl and Al) in the dried product were determined by inductively coupled plasma spectroscopy using an Agilent 5800 ICP-OES instrument.
[0243] The median size of the powder or suspension is measured using a laser particle size analyzer model LA950V2 sold by Horiba.
[0244] Manufacturing solutions
[0245] The following materials were used in the examples.
[0246] - gibbsite Al(OH)3 powder, with a median size equal to 1.6 μm, a purity greater than 99.5% by mass and a specific surface area equal to 5 m 2 / g, for Examples 1-5,
[0247] - Lithium hydroxide monohydrate (LiOH, H2O), purity greater than 99.5% by mass, for Examples 2-5,
[0248] -Lithium chloride LiCl, purity greater than 99.5% by mass, for Examples 1-5,
[0249] - hydrochloric acid HCl, purity greater than 99% by mass, in 16M aqueous solution, for Examples 2-5,
[0250] - Ammonium alginate, purity greater than 99% by mass, for Examples 2-5.
[0251] The product of Example 1 outside the present invention and according to the teaching of U.S. Patent No. 4,348,295 is the product of Example 1 of U.S. Patent No. 4,348,295 and is obtained as follows:
[0252] 50 g of gibbsite were added to 200 ml of a 20 wt% LiCl solution, and the resulting mixture was then stirred at 115° C. for 2 hours.
[0253] The resulting mixture was filtered at ambient temperature (below 50° C.) on a Buchner funnel using filter paper with a permeability equal to 2 μm, so as to obtain a slurry.
[0254] The products of Examples 2 to 5 are obtained in the following manner:
[0255] In step a), for each example, 500 g of aluminum hydroxide are added to 2,000 g of water and ground for 75 minutes in a LabStar mill sold by NETZSCH at a temperature equal to 25° C. At the end of step a), the aluminum hydroxide suspended in the water has a median size of 0.55 μm.
[0256] In step b), for each example, (LiOH, HO) is added to the mixture obtained at the end of step a) so that the molar ratio between the OH provided by (LiOH, HO) and the Al initially present in the mixture is as described in Table 1. The temperature at which this step takes place, the mixing time and the pH of the mixture measured at the end of this step are also described in Table 1 for each example.
[0257] In step c), for each example, LiCl was added to the mixture obtained at the end of step b) so that the molar ratio between the Cl provided by LiCl and the Al initially present in the mixture was as described in Table 1. The temperature and mixing time at which this step took place are described in Table 1 for each example.
[0258] At the end of step c), the amount of lithium in the mixture, expressed as the Li / Al molar ratio, is as reported in Table 1.
[0259] In step d), the mixture is heated to a temperature T1 by a heating plate, and time t1 is the time during which the mixture is at a temperature greater than or equal to 50° C. Table 1 describes the temperature T1 and the time t1 for each example.
[0260] In step e), for each example, the mixture was heated at a constant temperature T 21 Table 1 describes the temperature T of each example. 21 and time t2.
[0261] In step f), for each example, HCl is added to the mixture obtained at the end of step e), so that the pH of the mixture decreases to the value indicated in Table 1, the Cl / Al molar ratio in the mixture after the addition of HCl having the value indicated in Table 1, during step f) at a temperature equal to T 31 The temperature of the acid introduced is kept constant, and time t3 is the time the mixture is at a temperature greater than or equal to 50°C. 31 and t3 as described in Table 1.
[0262] In step g), for each example, the mixture was filtered through a Buchner funnel at ambient temperature (less than 50°C) with a filter paper having a permeability of 2 μm to obtain a paste. The time t4 during which the mixture was at a temperature greater than or equal to 50°C is described in Table 1.
[0263] For each embodiment, time t5 which is equal to the sum of time t1 + t2 + t3 + t4 is also described in Table 1.
[0264] Table 1 below summarizes the parameters used in the manufacturing steps of Examples 2-5.
[0265] [Table 1]
[0266]
[0267]
[0268] (*): Outside the present invention
[0269] The various pastes obtained had the properties shown in Table 2 below.
[0270] [Table 2]
[0271]
[0272] (*): Outside the present invention
[0273] The products of Examples 2 and 3 consisted of more than 99 mass % of water, lithiated bayerite and LiCl.
[0274] The products of Examples 4 and 5 consisted of more than 99 mass % of water, lithiated bayerite, gibbsite and LiCl.
[0275] For each example, the paste obtained was then shaped in the following manner.
[0276] For Example 1, the paste obtained after filtration was spread on a metal grid, 1 mm thick and perforated with circular holes of 1.5 mm diameter, which was then scraped with a spatula on each side of the grid so that the paste filled the holes of the grid. This grid is then called "loaded". Once the grid is loaded, it is placed under a hot air circulation at 60°C, which makes it possible to "release" the grid, the object formed falling into a container placed under the grid. The object obtained is in the form of a cylinder with an average length equal to 0.8 mm and an average diameter equal to 1.4 mm.
[0277] For Examples 2 to 5, in step h), a starting charge is prepared consisting of the paste obtained at the end of step g) and ammonium alginate having a content equal to 1% by weight, based on the weight of the starting charge after drying at 200° C. for 16 hours at atmospheric pressure.
[0278] The paste and ammonium alginate were mixed in a planetary mixer for 120 minutes under hot air generated by a hot stripper set at a temperature equal to 100° C., so as to obtain a homogeneous starting charge and with a water content compatible with the shaping technique.
[0279] The starting charge is then spread on a metal grid of 1 mm thickness and perforated with circular holes of 1.5 mm diameter, then scraped with a scraper on each side of the grid so that the starting charge fills the holes of the grid. The grid is then called "loaded". Once the grid is loaded, it is placed under a hot air cycle at 60°C, which makes it possible to "release" the grid, the object formed falling into a container placed under the grid. The object obtained is in the form of a cylinder with an average length equal to 0.8 mm and an average diameter equal to 1.4 mm.
[0280] According to the present invention, Examples 2 and 3 have high lithium absorption capacity.
[0281] According to the invention, the shaped objects of Examples 2 and 3 have a greater lithium absorption capacity than the shaped object according to the prior art of Example 1. This comparison also highlights the importance of limiting the temperature to 60° C. in the production process of the product.
[0282] Comparison of Example 4 outside the present invention with Example 3 according to the present invention shows that in Example 4, the temperature in step e) is 60°C for a time t5 equal to 35 minutes (during which time the mixture is at a temperature greater than or equal to 50°C), resulting in a product with a cumulative content of aluminum hydroxide and boehmite of 30%, which limits its ability to adsorb lithium.
[0283] Of course, the present invention is not limited to the described embodiments, which are provided for illustrative purposes only.
Claims
1. A product comprising: - Water, and - crystallites, at least a portion of which, preferably all of which, consist of lithiated bayerite, The average size of lithiated bayerite crystallites is 10 nm or more and 25 nm or less, and The product has a combined aluminum hydroxide and boehmite content of 10% or less, The product contains at least the elements Li, Cl, Al, O and H, The elements Li, Cl and Al are present in the dry product in the following contents, determined by inductively coupled plasma spectroscopy and expressed in weight percentages: -2% <Li<5%, -10%<Cl<26%, -15%<Al<30%。 2. The product according to the preceding claim, having the following chemical analysis, in % by weight, determined on the dry product by inductively coupled plasma spectroscopy: -2% <Li<5%, -10%<Cl<26%, -15%<Al<30%, - Elements other than Li, Cl, Al, O and H: <3%, -O and H: make up to 100%.
3. A product according to any one of the preceding claims, wherein: - a water content greater than 1% and less than 95%, and / or - Average size of lithiated bayerite crystallites less than 23 nm 4. A product according to any one of the preceding claims, wherein: - The cumulative content of aluminum hydroxide and boehmite is less than or equal to 8%, and / or The crystalline phase comprises lithiated bayerite, boehmite and / or aluminium hydroxide selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof.
5. The product according to any one of claims 3 or 4, wherein: - a water content greater than 5%, and / or - a water content of less than 80%, and / or The crystalline phase comprises lithiated bayerite and aluminium hydroxide selected from gibbsite, bayerite, triclinic gibbsite, nordstrandite and mixtures thereof.
6. A product according to the preceding claim, wherein: - a water content greater than 10%, and / or - a water content of less than 70%, and / or -The only crystalline phase is lithiated bayerite.
7. The product according to any one of the preceding claims, consisting of at least 80% by weight of water and lithiated bayerite crystallites, aluminum hydroxide and / or boehmite, and LiCl and a binder.
8. The product according to the preceding claim, consisting of at least 80% by weight of water, and lithiated bayerite crystallites and aluminum hydroxide, and LiCl and a binder.
9. The product according to the preceding claim, consisting of a total of at least 80% by weight of water, lithiated bayerite crystallites, LiCl and binder.
10. The product according to any one of the three immediately preceding claims, wherein the binder is a polysaccharide, preferably an alginate.
11. A method for preparing a product according to any one of the preceding claims, the method comprising the steps of: a) an aqueous suspension of an aluminum source, preferably an aqueous suspension of a single aluminum source, the aluminum source being selected from boehmite or aluminum hydroxide and mixtures thereof, preferably aluminum hydroxide, if the median size of the aluminum source is greater than 3 μm, the aqueous suspension being ground to a median size of 3 μm or less, In this step a), the suspension is maintained at a temperature below 50°C; b) raising the pH by adding a base such that the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.20, and after adding the base, maintaining the mixture under stirring at a temperature below 50° C.; c) adding a chloride salt such that the molar ratio of Cl provided by the chloride salt to Al present in the mixture is greater than 0.25, and after the introduction of the chloride salt, maintaining the mixture under stirring at a temperature below 50° C.; the base in step b), the chloride salt in step c) and their respective amounts are selected so as to provide an amount of lithium in the mixture such that the Li / Al molar ratio is greater than or equal to 1; d) raising the temperature of the mixture to a temperature greater than or equal to 50° C. and less than or equal to 60° C., time t1 being the time during which the mixture is at a temperature greater than or equal to 50° C.; e) maintaining the mixture at a temperature greater than or equal to 50° C. and less than or equal to 60° C. for a time period t2; f) optionally, adding an acid to the mixture under stirring so as to reduce the pH of the mixture to 8 or less, the chloride salt in step c), the acid and their respective amounts being selected so that the Cl / Al molar ratio in the mixture is greater than or equal to 1, the mixture being maintained at a temperature less than or equal to 60° C., the time t3 being the time the mixture is at a temperature greater than or equal to 50° C., and if the process does not comprise said step f), the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is greater than or equal to 0.5; g) optionally and preferably filtering the mixture to obtain a paste, said mixture being kept at a temperature less than or equal to 60° C., time t4 being the time the mixture is at a temperature greater than or equal to 50° C.; The accumulated time t1+t2+t3+t4=t5 is greater than or equal to 45 minutes and less than 15 hours.
12. Process for the preparation of a product according to the preceding claim, wherein in step a) grinding of an aqueous suspension of an aluminum source chosen from boehmite or aluminum hydroxide and mixtures thereof is carried out to obtain a median size of ≤ 1 μm.
13. The method according to any one of claims 11 to 12, wherein the time t5 is such that the times t1, t2, t3 and t4 satisfy the following relationship: [t1 / (-1.2T1+75)]+[t2 / (-1.2T 20 +75)]+[t3 / (-1.2T 30 +75)]+[t4 / (-1.2T 40 +75)]≤1 and [t1 / (-0.225T1+14.25)]+[t2 / (-0.225T 20 +14.25)]+[t3 / (-0.225T 30 +14.25)]+[t4 / (-0.225T 40 +14.25)]≥1, where T1 is the temperature reached by the mixture in step d), T 20 is the average temperature of step e), T 30 is the average temperature of step f), and T 40 is the average temperature of the mixture during time t4.
14. The method according to the preceding claim, wherein the time t5 is such that the times t1, t2, t3 and t4 satisfy the following relationship: [t1 / (-0.8T1+50)]+[t2 / (-0.8T 20 +50)]+[t3 / (-0.8T 30 +50)]+[t4 / (-0.8T 40 +50)]≤1, and / or -Time t5 makes the times t1, t2, t3 and t4 satisfy the following relationship: [t1 / (-0.2T1+13)]+[t2 / (-0.2T 20 +13)]+[t3 / (-0.2T 30 +13)]+[t4 / (-0.2T 40 +13)]≥1.
15. The method according to the preceding claim, wherein the time t5 is such that the times t1, t2, t3 and t4 satisfy the following relationship: [t1 / (-0.55T1+34.5)]+[t2 / (-0.55T 20 +34.5)]+[t3 / (-0.55T 30 +34.5)]+[t4 / (-0.55T 40 +34.5)]≤1.
16. The method according to any one of claims 11 to 15, wherein: - aluminum hydroxide, boehmite and mixtures thereof are the only aluminum sources used in all steps of the process, and / or - in step b), the molar ratio between the OH provided by the base and the Al present in the mixture is greater than 0.25 and less than 10, and / or - In step b), after adding the base, the pH of the mixture is greater than 9 and less than 13.
17. A method according to any one of claims 11 to 16, wherein: - in step c), the molar ratio between the Cl provided by the chloride salt and the Al present in the mixture is less than 10, and / or - the base in step b), the chloride salt in step c), and their respective amounts are selected to provide an amount of lithium in the mixture such that the Li / Al molar ratio is greater than 1.1 and less than 4, and / or - In step d), the time t1 is greater than 5 minutes.
18. A method according to any one of claims 11 to 17, wherein: - in step e), the temperature of the mixture is substantially constant, and / or - in step e), the time t2 is greater than 40 minutes, and / or - In optional step f), at least part of the amount of Cl necessary to obtain a Cl / Al molar ratio greater than 1 is provided by an acid.
19. The method according to any one of claims 11 to 18, wherein: - in optional step f), lowering the pH of the mixture to a value below 7.5 and above 6.5, and / or - in optional step f), setting the Cl / Al molar ratio in the mixture to a value less than 3, and / or - In optional step f), the temperature of the mixture is substantially constant.
20. The method according to any one of claims 12 to 19, wherein: - in optional step f), the time t3 is greater than 5 minutes, and / or - In step g), the time t4 is less than 15 minutes.
21. The process of claim 16, wherein aluminum hydroxide is the only source of aluminum used in all steps of the process.
22. The method according to any one of claims 11 to 21, wherein: - steps a) and b) are performed simultaneously, and / or - Steps a), b) and c) are carried out simultaneously.
23. The method according to any one of claims 11 to 22, comprising, after step g), a step h) of shaping the starting material comprising the paste obtained at the end of step g) into the form of an object or a coating, preferably in the form of an object, and an optional step i) of reducing the water content of said object or said coating.
24. The method according to the preceding claim, wherein in step h) the starting filler comprises a binder.
25. A method according to the preceding claim, wherein the binder is a polysaccharide comprising groups capable of forming ionic bonds with a gelling agent to form a gelling polysaccharide.
26. A method according to the preceding claim, wherein the polysaccharide is selected from alginates.
27. The method according to any one of claims 23 to 26, wherein steps h) and i) are performed at least partially simultaneously.
28. An apparatus for collecting lithium comprising a product according to any one of claims 1 to 10 or a product obtained by a method according to any one of claims 11 to 27.
Citation Information
Patent Citations
METHOD FOR PREPARING AN ADSORBENT MATERIAL AND METHOD FOR EXTRACTING LITHIUM FROM SALINE SOLUTIONS USING SAID MATERIAL
FR3053264A1
Crystalline lithium aluminates
US4348295A
